Carcass and Non-carcass Components of Priangan and Javanese Fat-tailed Rams Slaughtered at Mature Live Weight - M Baihaqi; R Herman (Media Peternakan, 2012)
Twenty-three of indigenous Priangan and Javanese Fat-tailed (JFT) ram breeds were used to evaluate its carcass and non carcass components slaughtered at mature live weight. Five Priangan rams and six JFT rams were slaughtered at 32.5 kg of live weight while six other rams of each breeds were also slaughtered at 40 kg of live weight. Before the rams were slaughtered, they werefattened using pellet ration which was formulated according to NRC for fattening 10 kg of lamb, containing 73.3% TDN and 16% protein in dry matter bases. Feed and water were given ad libitum. Rams were slaughtered and dissected when they reached their assigned slaughter weight (32.5 and 40 kg). The results showed that both breeds had high percentage of carcass (53%-55%) with no significantly different between breeds (P > 0.05) either were slaughtered at 32.5 kg or 40 kg. However, carcass of Priangan rams had significantly more muscle, but less fat than Javanese Fat-tailed rams at mature live weight (P < 0.05). Non-carcass components were not significantly different between breeds (P > 0.05) except for head, tail and testes (P < 0.01) and liver (P < 0.05). The edible and inedible portion of non-carcass rangedfrom 30%-32% and 12%-15% of slaughter weight, respectively.